1994
DOI: 10.1136/jech.48.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis: a waterborne outbreak affecting 1600 people in a small Danish town.

Abstract: Study objective -To examine (i) the extent of illness caused by contamination of a waterworks with waste water due to overflow, and its correlation with precipitation; (ii) the potential secondary spread; (iii) economic losses due to sick leave. Design -A historical follow up study with structured postal questionnaires. Setting -A small community on the outskirts of greater Copenhagen at the end of 1991 and the beginning of 1992.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…Despite wealthy economies and access to proven drinking water-treatment technologies significant outbreaks of waterborne intestinal disease have occurred in North America and Western Europe over the last 10-15 years [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite wealthy economies and access to proven drinking water-treatment technologies significant outbreaks of waterborne intestinal disease have occurred in North America and Western Europe over the last 10-15 years [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the problems of demonstrating NoV in water samples where collection time is usually delayed following "flash" contamination events, waterborne outbreaks often correlate with maintenance or emergency incidents, disinfectant failure or flooding at WTPs or wastewater treatment plants (WWTPs), heavy rain, or human error (20,33). Significantly, the first warning of waterborne infections may come through increased reporting of gastroenteritis from the public (28).…”
mentioning
confidence: 99%
“…They found that warmer temperatures and extreme rainfall were significant contributing factors to waterborne disease outbreaks in Canada . Similar studies have been conducted in England (Nichols et al 2009), the Netherlands (Schijven and de Roda Husman 2005), Finland (Miettinen et al 2001), Denmark (Laursen et al 1994), and Taiwan (Chen et al 2012). In many developing countries, lack of access to improved drinking water and sanitation exacerbates the impact of these extreme precipitation weather events on waterborne diseases.…”
Section: A) Waterborne Diseasesmentioning
confidence: 74%